The dynamics of supply and demand in a market directed economy with application to the Bicol River Basin - Vira Chankong; Drew, Donald R. (Bangkok : Asian Institute of Technology, 1974)
One of the major difficulties that seems to plague the success of any commodity production planning or a marketing planning is the long-term fluctuation of commodity price and production. This fluctuation is caused by the 'two coupled negative feedback structure which underlies the dynamics of supply and demand interactions within a market directed economy. The vast complexity added to this basic "two- loops" structure brings about the need for systematic approaches and dynamic planning for -efficient guidance and control of a market system. In this research, a dynamic simulation model characterizing the supply-demand interactions in a commodity market system is developed . using the systems dynamics approach. The Philippines rice market is taken as the particular case study. The model is a possible extension of the Dynamic Commodity Cycle Model (MEADOW, 1970) with three types of marketing channels; government, cooperatives and middleman, incorporated. Import and export are also included. The model is validated and various policies concerning price stabilization, import-export and retail-to-farm price margin are tested The utility of the model is that it can be used either as a mean for testing policies or as a forecasting device.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1974
Keywords: Commodity exchanges; Markets -- Philippine Islands -- Bicol River Basin; Economics